Vaccinology principles and practice - Morrow, John, 1949- (Wiley-Blackwell, 2012)
"This book addresses a profound deficiency in the field of vaccine research and development, namely the lack of a single volume describing the design and construction of vaccine strategies from first principles to implementation. This is an authoritative textbook that details a comprehensive and systematic approach to the science of vaccinology focusing on not only basic science, but the many stages required to commercialize and navigate the regulatory requirements for human application both in the United States and Europe. The book has broad appeal to clinicians, scientific and medical researchers alike, and graduate students"--Provided by publisher.